Financial development and income inequality - Ewa Weychert (Central European Economic Journal (CEEJ), 2020)
This paper analyses the influence of financial development on income inequality. Throughout this work, one may find the overview of theoretical and empirical literature as well as the empirical model using fixed panel data method. This research paper tries to disentangle the opposing views on the relationship between finance and income distribution, by evaluating the impact of the different dimensions of financial development on the level of income inequality. The important added value of this research is the usage of quintiles of income distribution as a dependent variable that may help to recognise the effect of financial development on the poorest and richest. Another novelty of the paper is the consideration of the effects of financial variables on Gini coefficient in the long and short run. The main results of the analysis using dataset from 2003 to 2014 indicate that financial access decreases income inequality.
Keywords: D63; G10; G20; 330; income inequality; financial development; access to finance; financial depth; financial stability; efficiency of financial sector